Constraint-driven local deformation optimization method for toolpath in the singularity region of five-axis machining - Chen, Liangji; Wang, Guihai; Lian, Haocheng; Huang, Zhijin; Xu, Haohao; Li, Huiying (Engineering Research Express, 2025)
Five-axis CNC machining plays a crucial role in manufacturing complex freeform surfaces with high precision and efficiency. However, when the tool axis vector enters a singular region, abrupt rotary axis motion occurs, causing severe degradation of machining accuracy and surface quality. To address this problem, this paper conducts an in-depth analysis of the causes of singular phenomena in five-axis machining and proposes a constraint-driven local deformation optimization algorithm for tool paths. First, based on the kinematic model of an A–C dual rotary table five-axis machine tool, the differential motion relationship between tool pose in the workpiece coordinate system and machine axis positions is derived. From the perspective of differential motion, the mechanism of singularity occurrence and its negative impact on machining accuracy are explained, and the singular region is explicitly defined. Subsequently, for tool axis vector points located within and on the boundary of the singular region, B-spline interpolation modeling is employed. Under the constraints of singular region avoidance, machine kinematic performance, and motion continuity, an optimization model is established with the objectives of minimizing tool axis vector deviation and minimizing the integral squared norm of the B-spline curve’s angular jerk. The optimal B-spline control points are obtained using a sequential quadratic programming (SQP) algorithm. Finally, simulation and machining experiments are conducted to validate the proposed method. Simulation and cutting tests show that the optimized toolpath avoids singular regions and improves motion smoothness, reducing C-axis peak acceleration by 79.2% and surface roughness Ra by 86.8%.